Late‐onset behavioral variant of frontotemporal lobar degeneration versus Alzheimer's disease: Interest of cerebrospinal fluid biomarker ratios. Issue 3 (27th June 2015) - Marelli, Cecilia; Gutierrez, Laure‐Anne; Menjot de Champfleur, Nicolas; Charroud, Celine; De Verbizier, Delphine; Touchon, Jacques; Douillet, Patrice; Berr, Claudine; Lehmann, Sylvain; Gabelle, Audrey
Abstract: Introduction: Cerebrospinal fluid (CSF) biomarker ratios were never evaluated in late‐onset (>65 years) behavioral variant of frontotemporal lobar degeneration (bvFTLD) versus Alzheimer's disease (AD). Methods: A retrospective monocentric study on 44 clinically suspected amnestic AD or bvFTLD patients with onset after 65 years and available CSF and clinical data. Results: The final clinical diagnosis was AD (n = 28; 64%), late‐onset bvFTLD (n = 14; 32%), and others (n = 2; 4%). Applying the CSF cutoff total‐tau/Aβ1–42 of 1.06, all the bvFTLD were in the FTLD range (<1.06, bvFTLD/FTLD), whereas the AD patients were either in the AD (>1.06, AD/AD) or in the FTLD range (<1.06, AD/FTLD); CSF biomarkers were significantly different in these three groups, but not neuroradiological features or presence of episodic memory deficit. Discussion: Late‐onset bvFTLD is underdiagnosed. The available CSF biomarker ratio cutoff need further improvement and overestimated late‐onset bvFTLD but could potentially differentiate it from AD, notably in case of conflicting results.